RENEWABLE ENERGY FOR NEWFOUNDLAND AND LABRADOR POLICY FORMULATION AND DECISION MAKING - BOKSH, Muktadir F. I. M. (Journal of Environmental Management and Tourism, 2016)
Newfoundland and Labrador province is blessed with many natural resources. The province heavily depends on nonrenewable petroleum products for its domestic need and export. Considering the limited nature of the nonrenewable resources, the provincial government has taken many policy initiatives to develop its renewable energy sector. It has been found that the concentration was mainly on hydroelectric generation where the government is now implementing the formulated policies. But, policymakers are in policy formulation stage for wind energy development. Overall, the province has set its long term vision of sustainable energy supply and moving towards development of clean and environment friendly energy.
Keywords: renewable energy; policy formulation; Newfoundland and Labrador